Pengaruh Kualitas Pelayanan dan Harga terhadap Kepuasan Konsumen Warunk Upnormal - Dalimunthe, Theresia Josephin (Publikasi Indonesia, 2025)
The low achievement in students' mathematics learning remains a persistent issue in education, primarily due to conventional teaching methods that fail to engage students actively. This study aims to examine the effect of the cooperative learning strategy, specifically the Teams Games Tournament (TGT) model, on the mathematics learning outcomes of eighth-grade students at SMP Negeri 1 Uwapa. The research employed a quantitative approach with a quasi-experimental method using a pretest-posttest control group design. The sample consisted of two purposively selected classes: one experimental group that received instruction through the TGT model and one control group taught using conventional methods. Research instruments included a validated multiple-choice test and observation sheets of student learning activities. The results revealed a significant improvement in the experimental group’s learning outcomes compared to the control group, with a posttest average score of 83.00 and a statistically significant difference according to the t-test (p < 0.05). Additionally, the TGT model enhanced student participation, motivation, and classroom interaction. These findings indicate that the TGT strategy effectively fosters an engaging learning environment and supports optimal student achievement. The implication of this research suggests that mathematics teachers are encouraged to implement the TGT model as an innovative teaching alternative, particularly in regions facing educational challenges.